2021
DOI: 10.48550/arxiv.2105.06876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The End of a Black Hole's Evaporation -- Part II

Farshid Soltani,
Carlo Rovelli,
Pierre Martin-Dussaud

Abstract: We derive an explicit expression for the transition amplitude from black to white hole horizon at the end of Hawking evaporation using covariant loop quantum gravity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…(26) It represents one of the many routes of the transformation from the black hole to the white hole. [35][36][37][38][39][40][41][42][43] It is interesting that while the formation of the gravitational white hole has extremely small probability, in hydrodynamic analog gravity the white hole horizon is easily formed as the hydraulic jump in the flowing shallow water. [44][45][46][47][48] All the considerations above demonstrated that the factor (1 + Q 2 /r 2 ) in Eqs.…”
Section: Entropy In Approach Based On the Singular Coordinate Transfo...mentioning
confidence: 99%
“…(26) It represents one of the many routes of the transformation from the black hole to the white hole. [35][36][37][38][39][40][41][42][43] It is interesting that while the formation of the gravitational white hole has extremely small probability, in hydrodynamic analog gravity the white hole horizon is easily formed as the hydraulic jump in the flowing shallow water. [44][45][46][47][48] All the considerations above demonstrated that the factor (1 + Q 2 /r 2 ) in Eqs.…”
Section: Entropy In Approach Based On the Singular Coordinate Transfo...mentioning
confidence: 99%
“…A theory of quantum gravity must give the transition probability W (M, Q, r P , τ BH , τ t ) between the black hole state and the white hole state. For the formulation of this computation in Loop Quantum Gravity, see [5,6,10,28] A non-time-reversal-symmetric bounce can be obtained by having b and (v P , u P ) on different constant t surfaces and P and P at different radius. This gives u P = −v P and τ W H = u b − u P different from τ BH .…”
Section: The Reissner-nordstr öM Black To White Transitionmentioning
confidence: 99%
“…The spacetime described above is characterized by the region (u P < u < u P , v P < v < v P ) where the Einstein equations are not satisfied. Following [10], we call this region the B region. As mentioned in the introduction, this is the region where we assume quantum mechanics alters the classical spacetime dynamics.…”
Section: The Point P and The Onset Of The Tunnellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation of spin and intertwiner labels, the difficulty of dealing with non-compact gauge groups and the difficulties with working outside of the saddle-point approximation of the semiclassical regime are all factors that limit the understanding of anything but the simplest configurations. This is an unfortunate situation since it is expected that non-trivial configurations are needed to study the dynamics of the theory or to model possible quantum gravitational phenomena [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%